Environmental Ethics as an Ascetic Practice in the Age of Technology - Bacevičiūtė, Danutė (Filosofia, 2019)
This paper deals with the asceticism as a strategy of environmental ethics in the late modernity. This strategy can be observed in various political and civic initiatives as measure for reducing excess consumption as well as in various spiritual ecological practises. The extraordinary increase in the power of technology extends our responsibility, limiting it at the same time to a negative kind of action, i.e. an action in which what should not be done is much more obvious than what should be done. The authors who examine the late modernity (Bruno Latour, Ulrich Beck) usually look for ‘technological’ or ‘institutional’ solutions to the ecological crisis, and the question of the responsible subject becomes only one of the variables in the risk management equation. This paper proposes to look for a solution to the crisis of responsibility by posing again a question on the genesis of the ethical subject through the lens of Michel Foucault’s concept of asceticism as ‘technology of the self’.